Clinical predictors of prosthesis-patient mismatch after aortic valve replacement for aortic stenosis (Clinics, 2012)
OBJECTIVE: We sought to ascertain predictors of Patient Prosthesis Mismatch, an independent predictor of mortality, in patients with aortic stenosis using bioprosthetic valves. METHOD: We analyzed 2,107 sequential surgeries. Patient Prosthesis Mismatch was calculated using the effective orifice area of the prosthesis divided by the patient's body surface area. We defined nonsignificant, moderate, and severe Patient Prosthesis Mismatch as effective orifice area indexes of .0.85 cm²/m, 0.85-0.66 cm²/m², and